2023
DOI: 10.1007/s40948-023-00567-7
|View full text |Cite
|
Sign up to set email alerts
|

Ductile–brittle quantitative evaluation of rock based on post-peak properties under true triaxial stress

Abstract: To quantitatively evaluate the influence of high true three-dimensional stresses on the ductile–brittle behaviours of rock in deep underground engineering, a series of true triaxial compression tests with different stress levels were carried out on marble and four kinds of granite. The influences of true triaxial stress states (σ2, σ3) on the post-peak characteristics were analysed, and a new normalized ductile–brittle evaluation index was proposed based on post-peak energy conversion characteristics of rock u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The results are shown in Figure 4. It can be observed that under natural conditions, the brittleness values of red-bed sandstone increased by 18 17.85% compared to the natural state. Therefore, both in the natural state and under saturated conditions, the brittleness index of red-bed sandstone decreases with increasing confining pressure, which is consistent with the trend of decreasing brittleness with increasing confining pressure in rock masses.…”
Section: For Red-bed Sandstone Under Saturated Conditionmentioning
confidence: 95%
See 2 more Smart Citations
“…The results are shown in Figure 4. It can be observed that under natural conditions, the brittleness values of red-bed sandstone increased by 18 17.85% compared to the natural state. Therefore, both in the natural state and under saturated conditions, the brittleness index of red-bed sandstone decreases with increasing confining pressure, which is consistent with the trend of decreasing brittleness with increasing confining pressure in rock masses.…”
Section: For Red-bed Sandstone Under Saturated Conditionmentioning
confidence: 95%
“…Based on the definitions provided by existing scholars, this study considers brittleness and ductility as opposing characteristics [17,18]. The strain occurring in the rock mass prior to failure can be divided into recoverable elastic strain and irrecoverable plastic strain induced by crack propagation.…”
Section: A Methods To Evaluate the Brittleness In Consideration Of Pl...mentioning
confidence: 99%
See 1 more Smart Citation